2014
DOI: 10.1007/s10753-014-0037-5
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Serum Mannose-Binding Lectin Levels with the Development of Sepsis: a Meta-analysis

Abstract: Many studies have evaluated the association between serum levels of mannose-binding lectin (MBL) and sepsis; however, the findings are inconclusive and conflicting. For a better understanding of MBL in sepsis, we conducted a comprehensive meta-analysis. Potential relevant studies were identified covering Science Citation Index, the Cochrane Library, PubMed, Embase, CINAHL, and Current Contents Index databases. Two reviewers extracted data and assessed studies independently. Statistical analyses were conducted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 43 publications
1
15
0
1
Order By: Relevance
“…Our data were in line with the study of Auriti et al (21) and Liu and Ning (22), who reported that low MBL levels increased the risk of nosocomial sepsis. Our results were also concordant with the study of Gao et al (14), who described that sepsis in the infant subgroup had considerably lower MBL level than those in the controls in Asians and Caucasians. But our results were in apparent contrast to the high MBL expression reported in the neonates with necrotizing enterocolitis (20).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our data were in line with the study of Auriti et al (21) and Liu and Ning (22), who reported that low MBL levels increased the risk of nosocomial sepsis. Our results were also concordant with the study of Gao et al (14), who described that sepsis in the infant subgroup had considerably lower MBL level than those in the controls in Asians and Caucasians. But our results were in apparent contrast to the high MBL expression reported in the neonates with necrotizing enterocolitis (20).…”
Section: Discussionsupporting
confidence: 93%
“…The associations between MBL2 gene polymorphisms, circulating MBL levels, and susceptibility and out- comes in sepsis have been reported in several studies but have shown conflicting results (10)(11)(12)(13). Moreover, the concentrations of MBL may be diverse in patients with different ethnicities and ages (14). And little is known about the relationship between MBL and neonatal sepsis in the Chinese Han population.…”
Section: Introductionmentioning
confidence: 99%
“…The latter is activated by multimeric pattern recognition molecules (PRMs) comprising collagen and globular recognition domains and includes mannose-binding lectin (MBL), Ficolin-1, Ficolin-2 and Ficolin-3. MBL deficiency is associated with bacterial infections [8,9], but there are limited data regarding ficolins and infections. Nevertheless, decreased survival was found in septic patients with polymorphisms in the promoter region of the FCN1 gene [10], and survival tended to be lower in patients with community-acquired pneumonia and low Ficolin-2 level [11].…”
Section: Introductionmentioning
confidence: 99%
“…5,14,15 A recent meta-analysis reported that MBL levels in patients with sepsis were significantly lower than those in healthy participants. 15 Huh et al reported that although MBL levels in patients with severe sepsis were higher than those in patients with septic shock, MBL levels in nonsurvivors with septic shock were lower than those in survivors with septic shock. 16 However, Zhao et al reported that MBL levels in patients with sepsis with DIC upon arrival at the emergency department were higher than those in patients without DIC.…”
Section: Introductionmentioning
confidence: 99%